Online reputation management in destination and hospitality : what we know, what we need to know - Rialti, Riccardo; Kvítková, Zuzana; Makovník, Tomás (Bingley, U.K. : Emerald Publishing Limited, 2023)
Reputation is considered one of the most relevant assets in business. Tourism and hospitality are no exception - visitors rely heavily on reviews and feedback found on online platforms to inform their decisions. Online Reputation Management in Destination and Hospitality's comprehensive collection of research decodifies the best practices existing in the market, developing innovative strategies for tourism, hospitality, and destination managers to tailor marketing communication strategies to attract attention and boost their reputation. From identifying biased fake reviews to collecting data from the largest online reviewing platforms, Online Reputation Management in Destination and Hospitality analyses the importance of reputation for consumers and their decision-making. The authors provide guidance for destination and hospitality managers on best practices emerging from real-life scenarios combined with the latest theoretical work. Unique research by chapter authors contributes to an increasingly interdisciplinary field, making Online Reputation Management in Destination and Hospitality essential reading for researchers, managers, and business owners globally and across the tourism and hospitality sector.
Part I. Introduction -- Chapter 1. Online reputation management in tourism: Emerging themes, theories, problems and solutions / Riccardo Rialti, Zuzana Kvítková, and Tomas Makovnik -- Part II. Determinants of online reputation in tourism -- Chapter 2. The electronic word-of-mouth (ewom) focusing studies on tourism research / Kristína Medeková, Kristína Pompurová, and Ivana Šimocková -- Chapter 3. How have travelers' needs evolved because of the COVID-19 pandemic? Corporate reputation building in tourism industry on digital platforms / Mirko Olivieri, Elanor Colleoni and Giuseppe Bonaccorso -- Chapter 4. Big data and online reputation management in tourism: Leveraging the role of entrepreneurship / Diletta Vianello, Anna Marrucci, Cristiano Ciappei, and Claudio Becagli -- Chapter 5. Specifics of online reputation management of hotel services intermediaries and their role in reputation creation / Zuzana Kvítková and Zdenka Petru -- Chapter 6. Global impacts of online reputation management of pre- and post-coronavirus pandemic: Comparative analysis in context of industry 4.0 / Faheem Uddin Syed, Raffaele Donvito, and Gaetano Aiello -- Chapter 7. Factors affecting the tourists approach to health and safety information in reviews during the COVID-19 pandemic / Martin Vasko, Natalie Volfova, and Alzbeta Zikova -- Part III. Online reputation management strategies -- Chapter 8. How to boost reputation in growing museums? Evidence from an Italian case / Silvia Fissi, Elena Gori, and Alberto Romolini -- Chapter 9. Relevance of social media management in online reputation building in tourism and hospitality: Case of Finland / Natalia Kushcheva and Tiia-Mari Eilola -- Chapter 10. Reviews on the internet marketing communication of the spa tourism enterprises in Slovakia / Radka Marceková, Lubica Šebová, and Andrej Malachovský -- Part IV. Instruments to improve orm in destination management -- Chapter 11. Does tourist pressure influence the online reputation of a
Includes bibliographical references and index.
Print version record.
Keywords: Tourism -- Marketing; Hospitality industry -- Marketing; Internet marketing; Reputation; Business & Economics -- Industries -- Hospitality, Travel & Tourism; Tourism industry